CASPR2‐IgG‐associated autoimmune seizures. Issue 3 (15th January 2022) - Garrido Sanabria, Emilio R.; Zahid, Anza; Britton, Jeffrey; Kraus, Gregory J.; López‐Chiriboga, Alfonso Sebastian; Zekeridou, Anastasia; Flanagan, Eoin P.; McKeon, Andrew; Mills, John R.; Pittock, Sean J.; Dubey, Divyanshu
Abstract: Objective: This study was undertaken to report clinical presentations and outcomes of CASPR2‐IgG‐associated seizures. Methods: Mayo Clinic Neuroimmunology database was queried to identify CASPR2‐IgG‐seropositive (CASPR2‐IgG+) patients evaluated at our institution (2009–2019). Results: Of the 53 CASPR2‐IgG+ patients (titer ≥ 1:10), 20 had seizures (38%). All seizure patients were male, with median onset age of 68 years. Eighteen (90%) had seizures at initial presentation. One patient was found to have malignancy (colon adenocarcinoma). Two patients had coexisting LGI1‐IgG. Twelve patients had archived sera, which on titration had CASPR2‐IgG titers ≥ 1:100. Fifteen patients (75%) met criteria for autoimmune encephalitis. Patients most commonly presented with focal onset, nonmotor seizures with impaired awareness ( n = 14, 70%). Eleven patients also had focal motor and/or sensory seizures as one of the seizure semiologies. The majority of patients ( n = 11, 55%) developed generalized tonic–clonic seizures during their disease course. Seizure clusters occurred in 12 patients. In addition to seizures, patients developed cognitive disturbance ( n = 16, 80%), episodic emotional lability ( n = 13, 65%), paroxysmal dizziness ( n = 9, 45%), episodic ataxia ( n = 6, 30%), and chronic ataxia ( n = 9, 45%). Only three patients (15%) had coexisting peripheral nervous system involvement. Frontotemporal or temporal ictal and/or interictal electroencephalographic abnormalities were present among nine patients, and three had multifocal epileptiform abnormalities. Eight patients (40%) had medial temporal T2/fluid‐attenuated inversion recovery hyperintensity on brain magnetic resonance imaging. Elevated cerebrospinal fluid protein and/or lymphocytic pleocytosis was present in most cases (13/14, 93%). Thirteen patients reached seizure freedom following initiation of antiseizure medication (ASM; n = 4) or a combination of immunotherapy and ASM ( n = 9). Median duration of follow‐up was 25 months (range = 2–136 months). Significance: CASPR2‐IgG evaluation should be considered among older male patients with new onset focal seizures and impaired awareness often occurring in clusters with/without features of encephalitis. Coexisting neurological manifestations, including episodic emotional lability, ataxia, and paroxysmal dizziness, also aid in the diagnosis.